Etiological patterns of bacterial meningitis in neonatal sepsis - Setiawan, Andy; Amir, Idham; Tumbelaka, Alan R. (Paediatrica Indonesiana, 2016)
Background Sepsis and meningitis are major causes of mortality and morbidity in neonates. The prevalence of sepsis is around 1-4 out of every 1000 live births, and one-fourth is accompanied by meningitis. These numbers are higher in prematures. Objective To find out the prevalence and etiological patterns of bacterial meningitis in neonatal sepsis, and the pattern of antibi- otic susceptibility for organisms causing bacterial meningitis. Methods This was a cross sectional study, conducted in the neo- natal ward and emergency room at Cipto Mangunkusumo Hospi- tal from October 2003 to October 2004. Results Seventy two neonates fulfilled the inclusion criteria and were examined for blood and cerebrospinal fluid (CSF) cultures. Sixty out of 72 neonates were proven for sepsis. Bacterial menin- gitis was found in 18 neonates, and all cases were accompanied by sepsis. Positive CSF cultures were found in 12 neonates. The other six were diagnosed based on CSF cell count >32/Î¼l. Acinetobacter calcoaceticus was the major causative organisms in this study. The organisms were highly resistant to first line anti- biotics, except for chloramphenicol. They were also sensitive to ceftazidime (second line), meropenem, and imipenem. Conclusions The prevalence of bacterial meningitis in neonatal sepsis at Cipto Mangunkusumo Hospital was 18/60 in 2003-2004. The major causative organism was Acinetobacter calcoaceticus. Antibiotic resistance was very high and only chloramphenicol, ceftazidime, meropenem, and imipenem remain effective